Mama SASHA baseline survey. Report - International Potato Center (2011)
The Mama SASHA baseline survey is a key part of a project evaluation strategy aimed at assessing the impact of orange-fleshed sweetpotato (OFSP) on the health and nutritional status of women and children aged between 6and 23 months. Sub-Saharan Africa is one of the regions with the highest estimated prevalence rates of sub-clinical VAD and the risk is greatest among children less than five years of age and pregnant &lactating women. Introducing OFSP as an agriculture and local community action aims at improving and sustaining health and productivity. Past studies have shown potential of the OFSP to improve the vitamin A status of children less than2 years of age. The baseline survey was conducted from March to May 2011 in Bungoma and Busia counties of Western Province of Kenya. Busia County according to size related variables and were randomly assigned to the Control and Intervention areas. Specifically, the survey present data on; household demographic and socio economic characteristics, women knowledge and attitudes on vitamin A, nutrition, health care and sweetpotatoes, household farming & crop production, vitamin A rich-food consumption among the women and children aged 6-23 months, ANC and maternity utilization, nutritional status of the women and the children aged 6-23 months. Survey results indicate that the prevalence of VAD among the children as indicated by level of the retinol binding protein (RBP) of less than 0.825µmol/L was approximately 18%.We found that 47% and 33% of the children had attained the minimum DDS and minimum acceptable diet (as defined by WHO), respectively. Analysis of the 7-day food frequency consumption shows that the following were the most consumed food groups: cereals and tubers, vegetables and milk. Pulses were the least consumed food group. Consumption of sweetpotatoes was also relatively low (average of 1.7 different days per week) particularly that of OFSP (average of 0.1 different days in a week). Assessment of the nutritional status of the children indicated that, stunting affected 25% of children, with 8% being severely stunted; underweight affected 14% of children, with 4% being severely underweight; while wasting affected 7% of the children, with 2% being severe wasting.Mean BMI among the non-pregnant women was 22kg/m2: three quarters of the women were within the normal BMI range(18.5-24.9kg/m2), 10% were underweight (<18.5 kg/m2) and the remaining 15% were overweight (>25.0 kg/m2).Nutritional levels of women and children were particularly low in Bunyala District. Almost all the households (92%) planted sweetpotatoes and the average land under sweetpotatoes per household was 0.1 hectares. Generally, women’s knowledge concerning the value of deep orange fleshed sweetpotato variety was relatively low; 88% had no idea about the value of OFSP and only 9% knew about the vitamin A content of the variety.